2021
DOI: 10.1371/journal.pgph.0000088
|View full text |Cite
|
Sign up to set email alerts
|

Do community-based active case-finding interventions have indirect impacts on wider TB case detection and determinants of subsequent TB testing behaviour? A systematic review

Abstract: Community-based active case-finding (ACF) may have important impacts on routine TB case-detection and subsequent patient-initiated diagnosis pathways, contributing “indirectly” to infectious diseases prevention and care. We investigated the impact of ACF beyond directly diagnosed patients for TB, using routine case-notification rate (CNR) ratios as a measure of indirect effect. We systematically searched for publications 01-Jan-1980 to 13-Apr-2020 reporting on community-based ACF interventions compared to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Besides directly detecting TB, our case-finding campaigns also contained a strong community mobilisation component, and we observed sustained rates of care-seeking and TB diagnosis during all but the most restrictive period of pandemic lockdowns. As observed in other case-finding studies [20], increased TB awareness resulting from the study may have encouraged people to seek care for TB symptoms even if not directly screened, or increased clinicians’ index of suspicion for TB. In addition, the regular presence of research staff at local health facilities, and their inquiries about patients who had tested positive for TB and not yet started treatment, may have improved treatment initiation for patients diagnosed with TB through routine care.…”
Section: Discussionmentioning
confidence: 74%
“…Besides directly detecting TB, our case-finding campaigns also contained a strong community mobilisation component, and we observed sustained rates of care-seeking and TB diagnosis during all but the most restrictive period of pandemic lockdowns. As observed in other case-finding studies [20], increased TB awareness resulting from the study may have encouraged people to seek care for TB symptoms even if not directly screened, or increased clinicians’ index of suspicion for TB. In addition, the regular presence of research staff at local health facilities, and their inquiries about patients who had tested positive for TB and not yet started treatment, may have improved treatment initiation for patients diagnosed with TB through routine care.…”
Section: Discussionmentioning
confidence: 74%
“…Establishing collaborative efforts with community leaders can facilitate the dissemination of accurate information about TB, dispelling myths, and encouraging individuals to seek formal medical care promptly ( 48 ). The introduction of community screening programs is another key strategy to address delays in seeking treatment ( 49 ). By bringing TB testing and treatment closer to communities, these programs can overcome barriers related to geographical distance and contribute to early case detection.…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant impact of the ACF intervention or community TB prevalence survey (which is also a form of ACF, since it aimed to identify undiagnosed TB) on TB case-notifications, although our study had insufficient power to fully assess whether the observed 12% increase in bacteriologically-confirmed case notifications was significant or not. Our analysis of time trends suggests that there may have been a small peak in TB case notification rate after the intervention/prevalence survey in both arms followed by a dip, as would be expected with the substitution effect, whereby patients who would otherwise have been diagnosed routinely during the intervention period and immediately afterwards are instead found though ACF [ 12 ]. This substitution effect could account for the observed non-significant 12% increase in bacteriologically-confirmed case notifications and non-significant decreased case notifications for all registrations and all form TB.…”
Section: Discussionmentioning
confidence: 99%
“…Less intensive, enhanced case-finding (ECF) uses health information or awareness campaigns to encourage health-seeking behaviour when people experience TB symptoms, with or without access to diagnostics at community-level [ 10 ]. Evidence of an indirect effect, for example health promotion, may be reflected in prolonged increased TB notifications due to a change in testing behaviour through increased knowledge of symptoms and diagnosis, reducing TB stigma, changing social norms, or providing a prompt for symptomatic people to attend a health facility for testing [ 12 ]. Because of the high cost, and risk of false-positive and false-negative screening results, community-wide ACF is conditionally recommended only for general populations with undiagnosed TB of 500 per 100,000 population or higher [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation